1989
DOI: 10.1161/01.cir.80.2.314
|View full text |Cite
|
Sign up to set email alerts
|

Impaired chronotropic response to exercise in patients with congestive heart failure. Role of postsynaptic beta-adrenergic desensitization.

Abstract: The mechanism responsible for the attenuated heart rate (HR) response to exercise in patients with congestive heart failure (CHF) was investigated in 46 normal subjects and 59 patients with CHF stratified by peak exercise oxygen consumption (Vo2). The peak exercise HR and the increment in HR from rest to peak exercise were decreased in CHF patients, and both correlated strongly with peak Vo2 (r=0.810, p<0.0001; r=0.863, p <0.0001, respectively). Peak exercise norepinephrine level (NE) and the increment in NE f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
190
4
3

Year Published

1996
1996
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 336 publications
(206 citation statements)
references
References 36 publications
(4 reference statements)
9
190
4
3
Order By: Relevance
“…Although this is classically described in CHF [22], it has only been reported in one other study on PPH patients [4]. Chronotropic incompetence in CHF is believed to be due to downregulation of badrenoreceptors [22]. The same explanation may hold true in PAH patients, in whom downregulation of right ventricular myocardial b-adrenoreceptors has also been reported [23].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Although this is classically described in CHF [22], it has only been reported in one other study on PPH patients [4]. Chronotropic incompetence in CHF is believed to be due to downregulation of badrenoreceptors [22]. The same explanation may hold true in PAH patients, in whom downregulation of right ventricular myocardial b-adrenoreceptors has also been reported [23].…”
Section: Discussionmentioning
confidence: 93%
“…Although this is classically described in CHF [22], it has only been reported in one other study on PPH patients [4]. Chronotropic incompetence in CHF is believed to be due to downregulation of badrenoreceptors [22].…”
Section: Discussionmentioning
confidence: 96%
“…Colucci et al (20) demonstrated that the chronotropic response to exercise is strongly associated with maximal exercise capacity evaluated by VO 2 peak in patients with heart failure. Our post-left ventriculotomy patients had more impairment in the chronotropic response to exercise when compared to the heart failure patients.…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of maximal heart rate could be another mechanism contributing to the limited functional capacity of post-left ventriculotomy patients. Since chronotropic incompetence is associated with a desensitization of beta-adrenergic receptors in the sinus node (20), it is possible that partial left ventriculotomy does not improve this abnormality and patients would maintain a limited chronotropic response to exercise, further limiting functional capacity.…”
Section: Discussionmentioning
confidence: 99%
“…A ativação crônica do sistema nervoso simpático contribui para aumento da pós-carga, alteração do metabolismo energético miocárdico, levando a dano focal no miocárdio, com liberação de radicais livres com conseqüente produção de citocinas, que desempenharão papel importante na patogênese do remodelamento adverso do VE 47,48 . Esta ativação simpática pode ser constatada por níveis elevados de catecolaminas circulantes, que se associam com a gravidade 49 e são preditores potentes de mortalidade na IC 50 .…”
Section: Paradigmas Atuaisunclassified